Validation of the Violent Ideations Scale (VIS) in Spain - Urruela, Carlota (International journal of offender therapy and comparative criminology, 2023)
Research has shown that violent ideations (VIs) may play a key role in aggression and violence. However, there is no tool to measure this construct adapted to the Spanish language so far. The current study aims to translate and evaluate the psychometric properties of the Violent Ideations Scale (VIS) in European Spanish. This study counts with a convenience sample of 752 native Spaniards or Spanish speakers residing in Spain, between 18- and 75-years old, 53% identified as female and 47% identified as male. The dimensionality, gender measurement invariance, concurrent validity and reliability of scores were assessed. Initial evidence of external validity was collected. Results confirmed the unidimensionality of the instrument. Measurement invariance held across females and males and reliabilities were high. VIS-ES scores correlated with aggressive behavior during the previous month. The VIS-ES seems suitable for use in non-clinical Spanish speaking samples.